2015
DOI: 10.36076/ppj/2015.18.1
|View full text |Cite
|
Sign up to set email alerts
|

Perineural Dexamethasone Added to Local Anesthesia for Brachial Plexus Block Improves Pain but Delays Block Onset and Motor Blockade Recovery

Abstract: Background: Multiple studies have shown that perineural dexamethasone improves postoperative analgesia. However, some studies have shown minimal benefit, and have raised concerns regarding adverse physio-chemical effects of perineural dexamethasone. Furthermore, there is a paucity of studies wherein control (IV) dexamethasone was considered. Objective: The purpose of this meta-analysis was to evaluate the effectiveness of different concentrations of perineural dexamethasone injection on postoperative analgesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 0 publications
0
7
0
1
Order By: Relevance
“…Choi et al concluyen que la dexametasona prolonga el bloqueo de los AL de larga duraciónFinalmente cabe destacar una revisión de 2015 de Knezevic et al122 de 14 estudios prospectivos, aleatorizados, realizados sobre cirugías del miembro superior, en el que analizan el efecto analgésico de la dexametasona y la prolongación de la analgesia que esta produce, en función de la dosis de dexametasona aplicada a nivel PN y el AL empleado. Concretamente con ropivacaína, el AL utilizado en nuestro estudio, estiman una prolongación media de 638 minutos, sin objetivarse grandes diferencias entre el empleo de pequeñas dosis de dexametasona (4 mg) PN y altas dosis (8-10 mg) de la misma.…”
unclassified
“…Choi et al concluyen que la dexametasona prolonga el bloqueo de los AL de larga duraciónFinalmente cabe destacar una revisión de 2015 de Knezevic et al122 de 14 estudios prospectivos, aleatorizados, realizados sobre cirugías del miembro superior, en el que analizan el efecto analgésico de la dexametasona y la prolongación de la analgesia que esta produce, en función de la dosis de dexametasona aplicada a nivel PN y el AL empleado. Concretamente con ropivacaína, el AL utilizado en nuestro estudio, estiman una prolongación media de 638 minutos, sin objetivarse grandes diferencias entre el empleo de pequeñas dosis de dexametasona (4 mg) PN y altas dosis (8-10 mg) de la misma.…”
unclassified
“…Several perineural adjuncts (dexamethasone, dexmedetomidine and tramadol) have been tested in previous studies. However, none of them appears to be optimal in terms of offering effective and safe treatment 2‐4 . Thus, it is essential to dig out more potential adjuvants for replenishing the currently available evidence gap.…”
Section: Introductionmentioning
confidence: 99%
“…The analgesic effectiveness of nalbuphine has been demonstrated to be comparable to that of morphine, with a superior safety profile and fewer side effects 5 . Recently, several randomised controlled trials (RCTs) and meta‐analysis have convincingly demonstrated nalbuphine was a clinically effective adjunct in subarachnoid blocks, wound infiltration, epidural and caudal blocks 3,4,6‐8 . Nevertheless, because a quantitative meta‐analysis is unavailable, so the evidence strength based on single trial for perineural nalbuphine in BPB is far from sufficient.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations